Rice production handbook (Cooperative Extension Service, University of Arkansas, 1994)
The book presents a summary of research-based recommendations and an overview of Arkansas rice production. The aim of this book is to assist farmers in producing profitable, high yielding crops that enable growers to be competitive on the world market